TRIM65 Promotes Cervical Cancer Through Selectively Degrading p53-Mediated Inhibition of Autophagy and Apoptosis - Wang, Xiao-Yu; Mao, Hai-Wei; Guan, Xiao-Hui; Huang, Qi-Ming; Yu, Zhen-Ping; Wu, Jie; Tan, Hui-Lan; Zhang, Feng; Huang, Xuan; Deng, Ke-Yu; Xin, Hong-Bo (Frontiers in Oncology, 2022)
Tripartite motif containing 65 (TRIM65) is an E3 ubiquitin ligase that has been implicated in a variety of cellular processes as well as tumor progression, but its biological role and the underlying mechanism in cervical cancer is unclear. Here, we reported that TRIM65 expression in human cervical cancer tissues was significantly higher than that in the adjacent normal cervical tissues, and TRIM65 knockdown enhanced autophagic flux and autophagy-induced cell apoptosis, but not cell cycle, to dramatically inhibit the proliferation and migration of cervical cancer cells. Furthermore, our experiments showed that TRIM65 exhibited oncogenic activities via directly targeting p53, a tumor suppressor and a common upsteam regulator between autophagy and apoptosis, promoting ubiquitination and proteasomal degradation of p53. Taken together, our studies demonstrated that TRIM65 knockdown inhibits tumorigenesis and development of cervical cancer through inducing autophagy and autophagy-related apoptosis, suggesting that TRIM65 may be a potential therapeutic target for cervical cancer clinically.